Koroška leta 1919 in ozadje sprejetja odločitve o plebiscitu - britanski pogled in reakcije v slovenskem tisku - Osojnik, Janez (Studia Historica Slovenica, 2020)
On the one hand, the article, basing on the analysis of British sources and most relevant scientific literature, discusses events in the Southern part of Carinthia through the perspective of the Foreign Office of Great Britain which was, at the time, one of the countries who determined the post-war world. On the other hand, the article shows how the situation, especially the question of indivisibility of the Klagenfurt Basin, was viewed by the most important Slovenian papers. The article chronologically encompasses the period between the beginning of the year 1919 and the signing of the Saint Germain Peace Treaty, which sealed the fate of the Klagenfurt Basin with the plebiscite.
Keywords: 1919; Carinthia; diplomacija; diplomacy; Great Britain; Koroška; Koroški plebiscit 1920; Paris Peace Conference; pariška mirovna konferenca; plebiscite; politična zgodovina; slovenski časopisi; Slowenian newspaper; Velika Britanija